Limit theorems for multipower variation in the presence of jumps - Barndorff-Nielsen, O; Shephard, N; Winkel, M (2005)
In this paper we provide a systematic study of the robustness of probability limits and central limit theory for realised multipower variation when we add finite activity and infinite activity jump processes to an underlying Brownian semimartingale.